Cultural and psychological variables predicting academic dishonesty: a cross-sectional study in nine countries. Issue 1 (2nd January 2022) - Błachnio, Agata; Cudo, Andrzej; Kot, Paweł; Torój, Małgorzata; Oppong Asante, Kwaku; Enea, Violeta; Ben-Ezra, Menachem; Caci, Barbara; Dominguez-Lara, Sergio Alexis; Kugbey, Nuworza; Malik, Sadia; Servidio, Rocco; et al.
ABSTRACT: Academic dishonesty has serious consequences for human lives, social values, and economy. The main aim of the study was to explore a model of relations between personal and cultural variables and academic dishonesty. The participants in the study were N = 2, 586 individuals from nine countries (Pakistan, Israel, Italy, India, the USA, Peru, Romania, Ghana, and Poland). The authors administered the Academic Dishonesty Scale to measure academic dishonesty, the Kessler Psychological Distress Scale to measure distress, the Almost Perfect Scale – Revised to measure perfectionism, the Brief Self-Control Scale to measure self-control, and the Singelis Scale to measure independent self-construal. The results showed that the theoretical model was well fitted to the dataset in six countries: Pakistan, the United States, Romania, Ghana, Israel, and Poland. However, it was not well fitted in Italy, India, and Peru. Our results also showed that perfectionism significantly predicted academic dishonesty, but not in all countries. Self-control significantly predicted cheating, falsification, and plagiarism in the USA. Moreover, we found that distress was related to cheating o0nly in Ghana. Finally, independent self-construal predicted academic dishonesty. Our findings provide a cross-cultural contribution to the debate on academic dishonesty by highlighting its significant predictors and may inform interventions aimed at eliminating it. Our results can be used in preventing and curbing academic dishonesty. Knowledge on cross-cultural differences can be useful in international education for example, as an indicator accepting or relaxing attitude toward academic dishonesty in students from different countries.